1997
DOI: 10.1016/s0014-5793(96)01484-6
|View full text |Cite
|
Sign up to set email alerts
|

GAK: a cyclin G associated kinase contains a tensin/auxilin‐like domain1

Abstract: We have cloned a cDNA encoding a novel association partner of cyclin G by West-Western blotting. The cDNA encodes a protein that harbors a Ser/Thr protein kinase-like catalytic domain at the N-terminal. Hence, we named it GAK (cyclin G-associated kinase). The long C-terminal extension shares homology with tensin and auxilin, and contains a leucine zipper region. Co-immunoprecipitation and Western blotting showed that GAK and cyclin G associate together in vivo. GAK also co-precipitated with CDK5, and CDK5 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
167
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(169 citation statements)
references
References 36 publications
2
167
0
Order By: Relevance
“…A search of protein sequence databases using as a pattern the ␥-ear-and GGA-GAE-binding motif, ⌿G [PDE][⌿LM] (Mattera et al, 2004), revealed two sequences fitting this motif, FGPL and FGEF, within a protein known as GAK or auxilin 2 (Kanaoka et al, 1997;Kimura et al, 1997; Table 1 and Figure 1). Both sequences are contained within a relatively unstructured segment (designated clathrin-binding or CB) of the protein that also contains binding motifs for the clathrin terminal domain (i.e., DLL) and for the ear domains of the AP2-␣ and -␤2 subunits (i.e., DPF and WAAW; Mishra et al, 2004;Figure 1).…”
Section: Gak Contains Two Sequences Fitting the ⌿G[pde][⌿lm] Consensumentioning
confidence: 99%
See 1 more Smart Citation
“…A search of protein sequence databases using as a pattern the ␥-ear-and GGA-GAE-binding motif, ⌿G [PDE][⌿LM] (Mattera et al, 2004), revealed two sequences fitting this motif, FGPL and FGEF, within a protein known as GAK or auxilin 2 (Kanaoka et al, 1997;Kimura et al, 1997; Table 1 and Figure 1). Both sequences are contained within a relatively unstructured segment (designated clathrin-binding or CB) of the protein that also contains binding motifs for the clathrin terminal domain (i.e., DLL) and for the ear domains of the AP2-␣ and -␤2 subunits (i.e., DPF and WAAW; Mishra et al, 2004;Figure 1).…”
Section: Gak Contains Two Sequences Fitting the ⌿G[pde][⌿lm] Consensumentioning
confidence: 99%
“…Here we report that the AP1-binding, cyclin G-associated kinase (GAK; also known as auxilin 2; Kanaoka et al, 1997;Kimura et al, 1997;Greener et al, 2000;Umeda et al, 2000;Lee et al, 2005Lee et al, , 2006 specifically interacts with the ear domains of AP1-␥1 and -␥2 through two sequences fitting the ⌿G [PDE][⌿LM] consensus motif. More importantly, we demonstrate that this interaction is required for the association of GAK with the TGN and for the transport of the precursor of the acid hydrolase, cathepsin D, to lysosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclin G1 is associated with cyclin-dependent kinase 5 (CDK5) and non-CDK-serine/ threonin kinase, named cyclin G associated kinase (GAK). 3,4 In addition, cyclin G1 has been suggested to act as an oncogenic protein, because of its overexpression in human tumor cells. 5,6 On the other hand, cyclin G is also involved in G2/M arrest in response to DNA damage 7 or in the facilitation of TNF-induced apoptosis, 8 implicating tumor suppressive function.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclin G was shown to be associated with cdk5 in vivo (Kanaoka et al, 1997), but it is not clear whether cyclin G acts as a regulatory subunit of cdk5. It was also demonstrated that cyclin G can associate with the B' regulatory subunit of protein phosphatase 2A (Okamoto et al, 1996), as well as GAK, a non-cdk serine/threonine kinase (Kanaoka et al, 1997). It is not yet known, however, whether cyclin G regulates the activity of these enzymes or serves as their substrate.…”
Section: Introductionmentioning
confidence: 99%